Dari Jama'ah untuk Jama'ah: Makna Akuntabilitas Masjid - aufa, muhammad (JIATAX (Journal of Islamic Accounting and Tax), 2022)
As a public organization, the role of the mosque is required to be more than just a place of worship, but to be part of efforts to improve the welfare of the ummah. So then there needs to be accountability as a form of good mosque governance. This study aims to gain an understanding of the meaning of accountability for the presentation of mosque financial reports in Gresik district. This research method uses a qualitative research approach by presenting an interpretive paradigm. The study used in this research is transcendental phenomenology. Two informants have provided explanations of their experience in managing mosques. The results of this study reveal that the meaning of accountability for mosque managers is a form of responsibility received from the congregation for the prosperity of the congregation.